Unraveling the physical demands of rondo drills: how different formats shape acceleration and deceleration profiles - Silva, H.; Monteiro, J.; Baptista, J.; Beato, M. (The Journal of Strength and Conditioning Research, 2026)
Accelerations and decelerations are a critical component in the assessment of training demands in soccer. The characteristics of accelerations (>3 m·s-2) and decelerations (<-3 m·s-2) were compared across 3 structured rondo drills (4 vs. 1, 4 vs. 2, 5 vs. 2) performed during 8 minutes in different training sessions. Twenty male elite soccer players (age: 27.1 ± 6.1 years; height: 1.78 ± 0.06 m; body mass: 75.8 ± 7.6 kg) participated for a 10-week period using global navigation satellite systems sampling at 10 Hz. All efforts exceeding the acceleration (>3 m·s-2) and deceleration (<-3 m·s-2) thresholds were characterized by duration, magnitude, starting and ending speed, and distance covered. Linear mixed models with post hoc comparisons were used to identify differences between drills. Results showed that the frequency of actions increased with the number of players and pitch size. During the 4 vs. 1 format, players attained greater acceleration magnitudes and higher end speeds than the 4 vs. 2 (p < 0.001) and 5 vs. 2 formats (p = 0.003 and p = 0.009, respectively). They also accelerated for longer times and distances in 4 vs. 1 than in 4 vs. 2 formats (p < 0.01). Conversely, fewer differences were reported in decelerations, with 4 vs. 1 format registering higher magnitudes than the other formats (p < 0.01) and starting from higher speeds than the 4 vs. 2 format (p = 0.010). During all formats, players started accelerations and ended decelerations from similar, near-stationary speeds (<4 km·h-1, p < 0.05). These findings highlight that different rondo formats elicit distinct demands, particularly for accelerations. Therefore, rondos should be carefully planned according to session objectives, because their high intensity may contribute to fatigue and muscle damage, reinforcing the need for careful monitoring and integration within training.